Risk of Stunting in Children: Links to Internal and Social Family Interactions in Central Buton District (a Case Study) - Nangi, Moh. Guntur; Syukur, Muhamad; Suhaeb, Firdaus W.; Lestari, Sari Arie (Al-Hijrah Indonesia, 2023)
With a high prevalence of stunting in children in the Central Buton District. This study aims to explore the relationship between internal family dynamics and external social relationships affecting children's nutrition. The study was based on the hypothesis that more frequent and qualitative family interactions and involvement in social activities would correlate with a lower risk of stunting. This study used a cross-sectional study design. Analyzing secondary data from the 2021 Family Data Collection (PK21). The study included 6,586 target families as a sample, the analysis included family dynamics as an exposure variable and used the family happiness index formula to identify family interaction and social interaction. The study used logistic regression from Scikit-learn to evaluate the data in the final stage. Data analysis revealed that internal family interactions, although important, showed no statistically significant association with stunting risk (p=0.3699). However, social interaction had a highly significant association with reduced risk of stunting, with a regression coefficient of -1.9934 and Odds Ratio (AOR) of 0.1362 (95% CI: 0.0739 - 0.2510, p<0.0001) in logistic regression analysis. These findings confirm that strong social engagement and community support are key factors in reducing the prevalence of stunting among children in the Mawasangka sub-district. This study concludes that engagement in community social activities has a significant impact on reducing the risk of stunting in children. The findings suggest that interventions aimed at reducing stunting should go beyond intra-family interventions and include increased social interaction and community support to achieve optimal outcomes in stunting prevention.